Crescimento inicial e nutrição de cultivares de café arábica em ambiente controlado - Dias, Rafael Antônio Almeida (2021)
Balanced nutrition is necessary to achieve full coffee growth, development, and productivity. Brazilian coffee farming has used new cultivars launched by research institutes and universities. Thus, knowing the nutritional needs of the new cultivars is essential to establish precise and safe nutritional recommendations to express their maximum productive potential. The objective of this work was to evaluate the initial growth and nutrition of Arabic coffee cultivars in a controlled environment using different doses of nitrogen, phosphorus, and potassium. The experiments were installed in January 2018, in a greenhouse in the Experimental Field of EPAMIG, in Lavras-MG, on the campus of Universidade Federal de Lavras - UFLA. Three experiments were conducted using a completely randomized design, in a 3x4x4 factorial scheme, with three cultivars of Arabic coffee (Catuaí Vermelho IAC 144, MGS Ametista, and MGS Paraíso 2), in four doses (0, 50, 100, and 150%) of the tested nutrients (N, P, and K), based on the recommendation of Guimarães et al. (1999), in four replicates. In experiment 1, the doses of N were varied using urea as a source. In experiment 2, the doses of P were varied using triple superphosphate as a source. And in experiment 3 the K doses were varied using potassium chloride as a source. The plots consisted of one pot with one plant per pot. The characteristics evaluated were plant height, stem diameter, leaf area index in cm², and nutrient accumulation in the dry leaf matter. The experiment consisted of four seasons (every two months), the first assessment conducted in March 2018 and the last in December of the same year. In conclusion, cultivar MGS Paraíso 2 was more efficient in using N applied, with a greater gain in height, between the doses from 3 to 6 g plant-1 of N per pot, and less demanding in P, with a greater gain in height with the dose of 0 g plant-1 of P2O5 compared to the other cultivars evaluated. Cultivar Catuaí Vermelho IAC 144 was more demanding in N, with height gain superior to the others only in the dose of 9.99 g plant-1 of N, and more demanding in P, with a greater height gain with the dose of 15 g plant-1 of P2O5. The cultivar MGS Ametista showed less height gain than the cultivar Catuai Vermelho IAC 144 with the dose of 9.99 g plant-1 of N, showing no height gain in the different doses of P2O5 applied.